Breast osteoblast-like cells: a new biomarker for the management of breast cancer. Issue 9 (30th October 2018) - Scimeca, Manuel; Urbano, Nicoletta; Bonfiglio, Rita; Schillaci, Orazio; Bonanno, Elena
Abstract Background In this study, we investigated the relationship between the expression of the main in situ markers of breast cancer and the presence of breast osteoblast-like cells (BOLCs). Methods We collected 100 breast biopsies. Serial paraffin sections were obtained from each biopsy to perform histological classifications and immunohistochemical analyses (RUNX2, RANKL, vimentin, TGFβ, Ki67, CD44, ER, PR and HER2). Results Linear regression analysis showed a positive and significant correlation between the number of BOLCs and the expression of EMT-related markers (vimentin and TGFβ), Ki67 and ER. Conversely, we observed an inverse correlation between the number of CD44-positive breast cancer cells and the BOLCs. No significant differences were observed between the number of BOLCs and the HER2 scores. Conclusions Morphological and molecular characterisation of BOLCs can lay the foundations towards understanding the biological basis of the formation of breast microcalcifications, and breast cancer metastasis to bone. The data here reported may be useful for the identification of breast lesions with high potential to develop bone metastasis.